DAMPAK PEMBANGUNAN JEMBATAN BATURIJAL TERHADAP SISTEM PEMASARAN HASIL KELAPA SAWIT DI JORONG BATURIJAL NAGARI BATURIJAL KECAMATAN PADANG LAWEH KABUPATEN DHARMASRAYA - Yuyun Sri Handayani; Yurni Suasti; Deded Chandra (JURNAL BUANA, 2019)
This study aims to describe the impact of bridge construction on the marketing, transportation, and income systems of oil palm farmers in Jorong Baturijal Nagari Baturijal,Padang Laweh District. The type of research used is a type of combination research. With a research samples are 25 oil palm farmers. The results of the research obtained is the impact of bridge construction on the marketing system of oil palm products have changed.Before there is a bridge the community prefers to sell oil palm products to middlemen outside the Nagari Baturijal, whereas after the construction of more bridges choose in middlemen in the Nagari Baaturijal. The impact of bridge construction on the transportation of oil palm products is the shorter time and distance. The impact of bridge construction on the income of oil palm farmers is an average increase of 5%